The impact of feeding line on dairy production revenue - Vesna Očić; Branka Šakić Bobić; Zoran Grgić (Mljekarstvo)
In the Republic of Croatia declining trend in the number of milk suppliers is registered, (69.3 % decline in the year 2010 compared to the 2002). Since the EU expects to abolish production quotas in the future (after the years 2014/2015), and reduce different protections for milk producers, there will be a decrease in the price of European milk. According to some predictions price will decrease for 5-15 % in the most of the EU countries, and this will be subsequently reflected in the Republic of Croatia. Mentioned facts will force milk producers to maximize business rationalization. At dairy farm, the highest cost is for animal feed, it is an ideal starting point for the implementation of business rationalization procedures. Previous studies show that the production of own animal feed can reduce the feeding cost by 30-50 %, compared to purchased fodder. Therefore, this study seeks to determine the effect of different forage courses on dairy farm profitability and cost of milk per kg. To create a technological-economic model, which is used to calculate basic economic and technological parameters for the three types of commercial farms in Croatia, data from 210 farms from the Pannonian regions of Croatia was used. The existing forage feeding line and four recommended by experts (technologists) were taken into consideration. The results were used as input data for AHP multi-criteria analysis, which rankes feeding line. According to the overall feeding lines priorities for all three types of dairy farms, the rank will start with feeding line 3, which consists of a mixture of peas and grains, corn silage, barley, Italian ryegrass and DTS, while the worst option is existing feeding line.